PERAN SUBAK MERTABAYU DALAM ADAPTASI PERUBAHAN IKLIM UNTUK MENINGKATKAN PRODUKTIVITAS USAHATANI PADI SAWAH DI DESA MONAPA KECAMATAN MOWILA KABUPATEN KONAWE SELATAN - Winata, Gusti Ngurah Wirayuda; Rianse, Usman; Nalefo, La (Universitas Halu Oleo, 2024)
The objective of this study is to ascertain the role of Subak Mertabayu in climate adaptation, to increase the productivity of paddy rice farming in Monapa Village, Mowila Subdistrict, South Konawe Regency, Southeast Sulawesi Province. The informants for this study were selected via purposive sampling. The research informants are comprised of three distinct groups: stakeholders, subak administrators, and subak users. Data were collected through observation, in-depth interviews, and document analysis with the assistance of an interview guide. This study focuses on the role of Subak Mertabayu in paddy rice farming. The data were analyzed using descriptive qualitative methods by the Miles and Huberman model, comprising data reduction, data presentation, and conclusion drawing/verification. The findings indicate that Subak Mertabayu plays a pivotal role in assisting farmers in adapting to climate change. Through its institutional framework, Subak has implemented a range of adaptation strategies, including the adoption of efficient irrigation technology, diversification of crops, and the cultivation of resilient crop varieties. Moreover, Subak also assumes the responsibility of educating and counselling its members on sustainable agricultural practices that can mitigate the adverse effects of climate change on agricultural productivity.